2015
DOI: 10.1007/s10530-015-0913-4
|View full text |Cite
|
Sign up to set email alerts
|

A novel impact of a novel weapon: allelochemicals in Alliaria petiolata disrupt the legume-rhizobia mutualism

Abstract: Some introduced species become invasive by releasing novel allelochemicals into the soil, directly harming nearby plants and soil microbes. Alliaria petiolata (garlic mustard) is an invasive plant, well known to excrete a suite of phytotoxic and antimicrobial allelochemicals, including allyl isothiocyanate (AITC) and benzyl isothiocyanate (BITC). While the effects of these chemicals on plant-mycorrhizae mutualisms are well documented, the effects on other plant-soil microbe interactions, such as the legume-rhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 66 publications
1
10
0
Order By: Relevance
“…Interaction effect indicated that higher concentrations produced lower vigour index. The increased inhibitory effect at higher concentration of weed extract may be due to increase in the concentration of allelo chemicals like phenolic acids namely, P-hydroxy benzoic acid, p-coumaric acid, caffeic acid, o-coumaric acid and ferulic acid (Portales-Reyes, 2015). Similar results were noticed by Singh and Thapar (2003).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Interaction effect indicated that higher concentrations produced lower vigour index. The increased inhibitory effect at higher concentration of weed extract may be due to increase in the concentration of allelo chemicals like phenolic acids namely, P-hydroxy benzoic acid, p-coumaric acid, caffeic acid, o-coumaric acid and ferulic acid (Portales-Reyes, 2015). Similar results were noticed by Singh and Thapar (2003).…”
Section: Discussionsupporting
confidence: 78%
“…Allelopathy is the suppression of growth of one plant Adeleke 4305 species by another due to the release of toxic substances (Portales-Reyes et al, 2015;Cipollini et al, 2012). One of the studied aspects of allelopathy is the role of allelopathy in agriculture.…”
Section: Author(s) Agree That This Article Remain Permanently Open Acmentioning
confidence: 99%
See 1 more Smart Citation
“…, Lankau , Portales‐Reyes et al. , Cipollini and Cipollini ), hypothetically providing non‐mycorrhizal Alliaria a competitive edge against native species. Woody seedlings appear to be particularly sensitive to allelopathic effects of Alliaria , likely due to their strong reliance on mycorrhizae during early development (Rodgers et al.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of allelopathy in Alliaria, in particular, has received a great deal of research attention and concern about potential ecological impacts (reviewed in Cipollini 2016, Rodgers et al 2008a). The secondary compounds in Alliaria tissues that are associated with herbivore defense are also released into Alliaria-associated soil, where they have been demonstrated to inhibit both fungal and bacterial plant symbioses (Wolfe et al 2008, Cantor et al 2011, Lankau 2011a, Portales-Reyes et al 2015, Cipollini and Cipollini 2016, hypothetically providing non-mycorrhizal Alliaria a competitive edge against native species. Woody seedlings appear to be particularly sensitive to allelopathic effects of Alliaria, likely due to their strong reliance on mycorrhizae during early development (Rodgers et al 2008a, Lankau 2011a.…”
Section: Interspecific Associationsmentioning
confidence: 99%